2009
DOI: 10.4049/jimmunol.0901011
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine 1-Phosphate Receptor Agonist FTY720 Potently Inhibits Regulatory T Cell Proliferation In Vitro and In Vivo

Abstract: CD4+CD25+ regulatory T cell (Treg) entry into secondary lymphoid organs and local expansion is critical for their immunosuppressive function. Long-term application of the sphingosine-1 phosphate receptor agonist FTY720 exerts pleiotropic anti-inflammatory effects, whereas short-term FTY720 boosts antiviral immunity. In this study, we provide evidence that FTY720 potently inhibits Treg proliferation in vitro and in vivo without affecting their viability, phenotype, or in vitro immunosuppression. In contrast, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 53 publications
2
37
1
Order By: Relevance
“…In this study, we examined whether FTY720 and FTY720-P affect the immune function of Treg cells in vitro. In contrast to Wolf et al (21), we found that FTY720 did not affect the proliferation of the CD4 + CD25 + T cells. Though the proliferation of Treg cells in the high and medium dose FTY720-P group appeared to be enhanced slightly, there was still no significant difference between three FTY720-P groups and the control group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, we examined whether FTY720 and FTY720-P affect the immune function of Treg cells in vitro. In contrast to Wolf et al (21), we found that FTY720 did not affect the proliferation of the CD4 + CD25 + T cells. Though the proliferation of Treg cells in the high and medium dose FTY720-P group appeared to be enhanced slightly, there was still no significant difference between three FTY720-P groups and the control group.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies found that the S1P receptor agonist FTY720 could partly affect the immune function of CD4 + CD25 + Treg cells (19,20). However, one study found that the proliferation of Treg cells was impaired significantly by FTY720 (21). In this study, we examined whether FTY720 and FTY720-P affect the immune function of Treg cells in vitro.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…FTY720 modulates S1P signaling, preventing lymphocyte egress from the thymus and spleen into the blood and from the lymph nodes (LNs) into the lymph, thus blocking lymphocyte trafficking to target tissues (5,6). It also affects dendritic cell (DC) migration (16,31), modulates DC proinflammatory signaling, and is a potent inhibitor of regulatory T cell (Treg) proliferation (56). Controversy surrounds the complex mechanism of action of FTY720 in vivo, and it is unclear whether it acts as an agonist, a functional antagonist, or both during the regulation of lymphocyte recirculation (21,47,52,58).…”
mentioning
confidence: 99%
“…The expression of receptors for S1P in Th1 and Th2 cells has also been reported [101,102]. S1P 1 , S1P 3 , S1P 4 , and S1P 5 were found to be expressed in both cell types.…”
Section: Effects On T Cellsmentioning
confidence: 62%